Restrukturyzacja placówki medycznej - doświadczenia praktyczne - Kachniarz, Marian (Restructuring of the Medical Unit - Practical Experience, 2006)
In this article there were presented the theoretical chances to carry out the process of restructuring in medical posts. An analysis of the concrete restructuring process in powiat Kamienna Góra became the article's background.The author pointed at threats which are rising at the next stages of transformations and characterised the terminal effect of changes. However carrying out of such a process is complicated extremely and requires big organizational efficiency. It is necessary too: a cooperation of the management of the administrative district (powiats) and hospital's management and the crew's majorities, understanding for these changes on the regional level and professional legal service. Big benefits, mainly economic, are persuading to accept the thesis about the need to introduce this kind of transformations into the bigger scale.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1103, s. 85-97